Menkes disease – a rare disorder requiring interdisciplinary management - Jaworek, Magdalena; Hałubiec, Przemysław; Janeczko, Magdalena; Steczkowska, Małgorzata; Jaworek, Andrzej; Kroczka, Sławomir; Wojas-Pelc, Anna; Kwinta, Przemko (Pediatria Polska - Polish Journal of Paediatrics, 2025)
Menkes disease is a rare, X-linked recessive neurodegenerative disorder caused by mutations in the ATP7A gene, resulting in defective copper transport. The clinical picture is dominated by early-onset neurological decline, connective tissue abnormalities, and characteristic hair shaft defects. The aim of this report was to present the case of a 4-year-old boy diagnosed with Menkes disease based on clinical features, biochemical analysis, trichoscopy, and whole exome sequencing, which revealed a novel pathogenic ATP7A variant. Dermatological signs, including brittle, depigmented, and twisted scalp hair, were among the earliest disease indicators. This case highlights the importance of early suspicion based on subtle cutaneous signs, especially in the neonatal period. This case highlights that a multidisciplinary diagnostic approach – including dermatological, neurological, radiological, and genetic assessment – is critical for timely diagnosis, a condition necessary for successful prevention of disease progression. Early treatment with copper histidine may improve outcomes but remains limited to selected patients with residual ATP7A function.